PREPARATION OF UNDERGRADUATES ENROLLED IN ECONOMICS TO PROJECT ECONOMIC ACTIVITIES - N. Simonov (Вестник Северо-Кавказского федерального университета)
The article presents a description of the main features of the training of economic master students to project-economic activity. Features of project-economic activity and specificity of professional competences reflecting readiness and ability to it are shown. The article substantiates that the training of economic master students to project-economic activity is provided by the formation of appropriate professional competence, taking into account the specific content of the components that make up its structure - cognitive, motivational, value, behavioral and reflexive components.